Design, Synthesis, and Biological Evaluation of Benzo[cd]indol-2(1H)-ones Derivatives as a Lysosome-Targeted Anti-metastatic Agent - Li, Jinghua; Chen, Shuai; Zhao, Yancong; Gong, Huiyuan; Wang, Tong; Ge, Xiaoling; Wang, Yuxia; Zhu, Chenguang; Chen, Liang; Dai, Fujun; Xie, Songqiang; Wang, Chaojie; et al. (Frontiers in Oncology, 2021)
Lysosome has become a hot topic in tumor therapy, targeting the lysosome is therefore a promising strategy in cancer therapy. Based on our previous lysosome-targeted bio-imaging agent, homospermine-benzo[cd]indol-2(1H)-one conjugate (HBC), we further developed three novel series of polyamine- benzo[cd]indol-2(1H)-one conjugates. Among them, compound 15f showed potent inhibitory activity in hepatocellular carcinoma migration both in vitro and in vivo. Our study results showed that compound 15f entered the cancer cells via the polyamine transporter localized in the lysosomes, and caused autophagy and apoptosis. The mechanism of action revealed that the crosstalk between autophagy and apoptosis induced by 15f were mutually reinforcing patterns. Besides, 15f also targeted lysosomes and exhibited stronger green fluorescence than HBC, which indicated its potential as an imaging agent. To summarize, compound 15f could be used as a valuable dual-functional lead compound for future development against liver-cancer metastasis and lysosome-imaging.